Combined maternal KIR2DL4 and fetal HLA-G polymorphisms were associated with preeclampsia in a Han Chinese population - Ma, Yantuanjin; Qian, Yuan; Jiang, Hong; Meng, Haiyun; Wang, Yang; Yang, Yuling (Frontiers in Genetics, 2024)
Preeclampsia is the main cause of maternal and infant mortality and morbidity during pregnancy. Killer cell immunoglobulin-like receptor 2DL4 (KIR2DL4) and human leukocyte antigen G (HLA-G) play crucial roles in immune tolerance at the maternal-fetal interface. In this case‒control study, 154 maternal–fetal pairs were recruited, including 74 pairs with preeclampsia (56 of 74 pairs from family triads) and 80 pairs with a normal pregnancy (78 of 80 pairs from family triads). SNaPshot technology was used to detect genetic polymorphisms for 7 TagSNPs in the KIR2DL4 and HLA-G genes. Among the fetal HLA-G gene polymorphisms, rs9380142 (A vs. G: OR = 2.802, 95% CI = 1.761–4.458) and rs1063320 (G vs. C: OR = 1.807, 95% CI = 1.144–2.852) differed between the preeclampsia group and the control group. The transmission disequilibrium test (TDT) suggested that the differences in the rs9380142G/A polymorphism in foetuses between preeclampsia triads and control triads were due to differences in transmission from the parents (P = 0.001). There was no significant difference in the distribution of maternal KIR2DL4 alleles or genotype frequency between the preeclampsia group and the control group. Gene‒gene interaction analysis revealed that the combined genotypes of maternal rs649216-CC and fetal rs9380142-GG, maternal rs1051456-CG/GG and fetal rs9380142-GG, maternal rs34785252-CC and fetal rs9380142-AA/GA, and maternal rs34785252-CC/AA and fetal rs9380142-GG were associated with a significantly lower risk of preeclampsia. Therefore, this study suggested that the combination of maternal KIR2DL4 and fetal HLA-G polymorphisms was associated with preeclampsia in a Han Chinese population.